Research of reserves for increasing profitability of construction enterprises - Sorokina, L.V.; Hoyko, A.F. (Ways to Improve Construction Efficiency, 2020)
The article analyzes the trends of financial results of construction companies during 2010 - 2019 by studying the slope of the trend line in the periods before and after 2014. The configuration features and the parameters of the equations of trend dependences of the share of profitable enterprises by type of construction activity. For the slope coefficients of the trend equations, a cluster analysis was performed using the C-means method, and the reliability of the results of the obtained cluster partitioning was proved. The criteria for restoring the profitability of the construction industry are substantiated, which are based on the results of a cluster analysis of the share growth of profitable enterprises in terms of the main areas of construction activity. Authors conducted a study of the segment of consumers that use services of small construction enterprises, represented by urban households. The results of it allowed, first, to structure potential consumers of services for overhaul and construction depending on their resources, and secondly, to quantify the impact of key components of cash flow and current consumer cost on purchasing power of the analyzed segment, thirdly, to establish reserves to increase the income of contractors in the segment and the possibility of reducing them. By constructing and analyzing the configuration of the distribution curve of expenditures on capital repairs and construction of urban households, its inconsistency with the conditions of the Pareto rule was established: instead of 20:80, about 20% of income in the construction market segment is provided by 47% of the poorest households. The other part, almost 80%, is formed by 53% of households with higher incomes. The threshold value of household income per 1 person is substantiated, failure to achieve which leads to savings in costs for repair and construction services. Its value is 6,000 UAH / month in 2019 prices.